Polyaromatic Hydrocarbon Inclusion Complexes with 2-Hydroxylpropyl-β/γ-Cyclodextrin: Molecular Dynamic Simulation and Spectroscopic Studies - Norah S. Alsadun; Amira A. Alfadil; Abdalla A. Elbashir; FakhrEldin O. Suliman; Mei Musa Ali Omar; Amel Y. Ahmed (Molecules, 2024)
In aqueous and solid media, 2-HP-β/γ-CD inclusion complexes with poly aromatic hydrocarbon (PAH) Phenanthrene (PHN), Anthracene (ANT), Benz(a)pyrene (BaP), and Fluoranthene (FLT) were investigated for the first time. The inclusion complexes were characterized and investigated using fluorescence and 1HNMR spectroscopy. The most prevalent complexes consisting of both guests and hosts were those with a 1:1 guest-to-host ratio. The stability constants for the complexes of PHN with 2-HP-β-CD and 2-HP-γ-CD were 85 ± 12 M−1 and 49 ± 29 M−1, respectively. Moreover, the stability constants were found to be 502 ± 46 M−1 and 289 ± 44 M−1 for the complexes of ANT with both hosts. The stability constants for the complexes of BaP with 2-HP-β-CD and 2-HP-γ-CD were (1.5 ± 0.02) × 103 M−1 and (9.41 ± 0.03) × 103 M−1, respectively. The stability constant for the complexes of FLT with 2-HP-β-CD was (1.06 ± 0.06) × 103 M−1. However, FLT was observed to form a weak complex with 2-HP-γ-CD. Molecular dynamic (MD) simulations were used to investigate the mechanism and mode of inclusion processes, and to monitor the atomic-level stability of these complexes. The analysis of MD trajectories demonstrated that all guests formed stable inclusion complexes with both hosts throughout the duration of the simulation time, confirming the experimental findings. However, the flexible Hydroxypropyl arms prevented the PAHs from being encapsulated within the cavity; however, a stable exclusion complex was observed. The main forces that influenced the complexation included van der Waals interactions, hydrophobic forces, and C–H⋯π interaction, which contribute to the stability of these complexes.